Design and construction of a multipurpose wideband anechoic chamber - Chung, B.K.; Chuah, H.T. (2003)
An electromagnetic anechoic chamber has recently been constructed at the Multimedia University. It is designed to operate over a very wide frequency range from 30 MHz through 18 GHz. It can be used for electromagnetic compatibility (EMC) tests, antenna measurements, radar cross section (RCS) measurements, testing RF transceivers, calibration of scatterometers, and other electromagnetic research experiments. The geometry of the chamber is asymmetrical, consisting of a combination of rectangular and tapered volumes. The size of the chamber is about 64 ft x 32 ft x 24 ft high. Ease of construction and ease of lining of the absorbers were preserved so that the actual quietness is comparable to the theoretical simulation result. The transmitting source is placed at one end of the chamber, and the receiving antenna or object under test is placed in a designated quiet zone at the other end. The walls and ceilings are configured such that no first-order and or second-order reflections (except those reflected from the floor) will propagate into the quiet zone. Hence, less-expensive absorbers can be used to achieve the required wideband performance. Reflection from the floor is required by the international EMC standards for radiated electromagnetic interference (EMI) emission tests; therefore, the chamber is designed for this capability. However, absorbing material can be placed on the floor to convert a semi-anechoic chamber into a fully anechoic chamber for radar and antenna measurements.